On the trapping of vinylgold intermediates - Hashmi, A. Stephen K.; Dondeti Ramamurthi, Tanuja; Rominger, Frank (Advanced synthesis & catalysis, 2010)
An internal aryl-substituted ortho-alkynylphenol and a similar aniline with stoichiometric amounts of N,N′-bis(2,6-diisopropylphenyl)imidazol-2-ylidene-gold tosylate [(IPr)AuOTs] and triethylamine gave the aurated heterocycles as stable intermediates of the corresponding gold(I)-catalysed hydrooxylation and hydroamination reactions. X-ray crystal structure analyses of both products could be obtained. A similar internal alkyl-substituted ortho-alkynylphenol gave only the cycloisomerised product, no aurated intermediate could be detected.
First published: 15 April 2010
Gesehen am 27.03.2023